PEDAGOGICAL AND PSYCHOLOGICAL PRINCIPLES OF FORMING THE PROFESSIONAL IMAGE OF A MODERN TEACHER - Machynska, Nataliia; Blikhar, Viacheslav (Socio-economic relations in the digital society, 2025)
The article demonstrates the results of an empirical study on the formation of the image of a modern teacher as an important factor in the effectiveness of pedagogical activity. It is emphasized that the image of a teacher affects the success of the educational process, the motivation of students to learn, and the perception of a modern teacher by society. It is stated that the topic of image is generally studied in domestic scientific sources, in particular, this problematic issue is revealed through: the development of communication culture and the formation of emotional intelligence; ensuring stress resistance and transformation of the system of teacher training. The author analyzes various approaches to the definition of the concept of “conditions”, and, therefore, notes that in scientific sources, pedagogical conditions are interpreted as: a purposeful system that takes into account both external and internal factors that affect teaching and upbringing; interaction of circumstances under which the educational process is provided more effectively; a set of factors that favourably affect the pedagogical process, making it more effective. The article analyzes the results of an empirical study obtained through a survey of participants in the educational process (teachers and students) of Lviv schools. On the basis of these results, the article identifies the pedagogical conditions for the formation of the professional image of a modern teacher, in particular: creating an atmosphere of respect, understanding and support for each student in the educational environment of an educational institution; improving the personal qualities of a modern teacher; improving the professional training of a future teacher in a higher education institution; forming motivation for self-improvement, updating knowledge and skills; developing and improving digital competence; and enhancing legal awareness. Thus, the article clearly characterizes each of the identified conditions.
Keywords: pedagogical image; pedagogical and psychological conditions; motivation; professional activity; legal awareness